Gene expression and metabolic responses of HepG2/C3A cells exposed to flame retardants and dust extracts at concentrations relevant to indoor environmental exposures. (February 2016) - Zhang, Jinkang; Abou-Elwafa Abdallah, Mohamed; Williams, Timothy D.; Harrad, Stuart; Chipman, James K.; Viant, Mark R.
Abstract: Humans are routinely exposed to mixtures of flame retardants (FRs) from multiple sources including indoor dust. As a model to explore the potential effects of FR exposure from indoor dust on human health, the molecular responses of human hepatoma cells (HepG2/C3A cells) to a defined mixture of FRs and to a dust extract were investigated using multiple non-targeted omics approaches. A solvent extract of an indoor dust standard reference material SRM2585 was used as the surrogate dust sample, while a mixture of four FRs (TCEP, TCIPP, TDCIPP and HBCD) was used to mimic the FR mixture in the indoor dust. Cytotoxicity tests indicated there were no significant changes to cell viability or cell integrity after a 24- or 72-h exposure of HepG2/C3A cells to the FR mixture or to the dust extract. However, transcriptomics revealed changes in gene expression associated with the metabolism of xenobiotics (e.g. CYP1A1, CYP1A2, CYP2B6 ) in the dust extract group but not in the FR mixture group after a 72-h exposure. Few metabolic or lipidomic changes were detected in response to either the FR mixture or to the dust extract group. Given that the dust extract contained components that elicited a biological response, in contrast to the lack of response induced by the FR mixture, our findings suggest that the most likely causes of the molecular responses to indoor dust exposure lie in components other than the four FRs investigated, e.g. caused by PAHs or PCBs. Graphical abstract: Highlights: HepG2/C3A cells were exposed to dust extract and mixtures of flame retardants (FRs). TCEP, TCIPP, TDCIPP and HBCD were quantified in HepG2/C3A cells after exposure. Gene expression relevant to xenobiotics was changed in the dust extract group. Few significant metabolic changes were detected in response to FR mixtures. The lipidomic profile of HepG2/C3A cells was disrupted after exposure to 4 μM HBCD.